#metoo: The Good, the Bad, and the Backlash - Tranchese, Alessia (From Fritzl to #metoo: Twelve Years of Rape Coverage in the British Press, 2023)
I start this discussion in this chapter with an outline of the key points within the #metoo debate, looking at what, according to various scholars, has and has not been achieved since the hashtag went viral in 2017. This overview constitutes the context for the subsequent analysis and critical evaluation, which will look at how the press conceptualised #metoo, and how it shaped some of the wider discussions about the hashtag. In Chapter 11, it will focus on whether (and how) the widespread use of #metoo after 2017 affected the representation of violence against women in the British press compared to the previous years.
Keywords: Irina